Characteristics and Trends in Intentional Acetaminophen Intoxication in Adolescents Over Two Decades. (1st June 2016) - Caudron, M; Gosselin-Papadopoulos, R; Jamoulle, O; Swaleh, S; Taddeo, D; Frappier, JY
Abstract: BACKGROUND: Acetaminophen is a common drug used for self-poisoning in adolescents, and an important cause of acute liver failure in the pediatric population. Data regarding intentional acetaminophen intoxication in Canadian youths is limited. OBJECTIVES: The purpose of the study was to describe the characteristics of intentional acetaminophen intoxications in Canadian adolescents and evaluate its evolution over two decades. DESIGN/METHODS: We performed a retrospective chart review of intentional acetaminophen ingestions in adolescents (11-18 years old) hospitalized at a Canadian pediatric tertiary care centre between 1989 and 2009. We recorded the patients' sociodemographic data, as well as the characteristics, complications and treatments of the intoxications. Data was compared across approximately five year periods as a group, then in both sexes separately. RESULTS: A total of 383 cases were examined, 53 of which were in male patients and 330 in female patients. Given the small number of male patients, only female patients were included in this analysis. There were 200 cases within the time intervals 1 and 2 (1989-1993, 1994-1998) and 130 cases within the time intervals 3 and 4 (1999-2003, 2004-2009). Demographics were relatively constant across the time periods. Impulsive gestures were indicated as the motivation in almost 80% of cases, which remained stable over time (p=0.56). The ingestion of additional substances and the quantity of acetaminophen also remained constant over time (p=0.79 and p=0.46). Mean time to physician consultation significantly increased in time from 6h in interval 1 to 13.4h in interval 4 (p=0.0001). The proportion of ICU admissions, coagulopathy and multiple organ failures also increased across time intervals (p=0.01, 0.03 and 0.03 respectively). There was no definitive linear trend in cases of hepatitis, encephalopathy or acute kidney injury (p=0.26, 0.81 and 0.27 respectively). There were two deaths, and one liver transplant over the 21-year period. Treatment significantly changed over time with progressive increase in N-acetylcysteine use from 47.4% to 81.1% (p=<0.0001) and progressive decline in charcoal use from 70.2% to 17.6% (p<0.0001) in intervals 1 to 4. Poison centre consultations significantly increased in time from 14.4% in interval 1 to 67.7% in interval 4 (p<0.0001). CONCLUSION: We suggest that the apparent severity increase in adolescent acetaminophen intoxication is related to the progressive increase in time to physician consultation with associated delays in treatment. The changes in management observed over the 21-year period is likely reflective of the evolution and availability of treatment protocols. Furthermore, the increase in poison centre consultations may account for part of the decrease in treatment variability across patients.